2022
DOI: 10.3390/vaccines10111776
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Multiple Evanescent White Dot Syndrome (MEWDS) Following First Dose and Booster of the mRNA-1273 COVID-19 Vaccine: Case Report and Review of Literature

Abstract: To report a rare case of a patient with two recurrent episodes of Multiple Evanescent White Dot Syndrome (MEWDS) associated with the second dose and second booster of the mRNA-1273 COVID-19 vaccine (Moderna), and to perform a literature review on COVID-19-vaccine-associated MEWDS. Case Report: A 31-year-old female was evaluated for a temporal scotoma and photopsias that started two weeks after the second dose of the Moderna COVID-19 vaccine. Dilated fundus findings were remarkable for unilateral, small whitish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This patient had received the fourth booster vaccination 2 weeks prior during admission to a nursing hospital. Soifer et al 13 summarized 13 cases with COVID-19 vaccine-associated MEWDS and found that these patients had clinical features similar to the ndings in patients who developed MEWDS after other vaccinations. All three cases of MEWDS associated with COVID-19 and vaccination against the disease occurred in male patients, indicating a signi cant difference in sex distribution among the groups.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This patient had received the fourth booster vaccination 2 weeks prior during admission to a nursing hospital. Soifer et al 13 summarized 13 cases with COVID-19 vaccine-associated MEWDS and found that these patients had clinical features similar to the ndings in patients who developed MEWDS after other vaccinations. All three cases of MEWDS associated with COVID-19 and vaccination against the disease occurred in male patients, indicating a signi cant difference in sex distribution among the groups.…”
Section: Discussionmentioning
confidence: 80%
“…[7][8][9][10] Case reports have described the occurrence of MEWDS after episodes of COVID-19 and vaccination against the disease. [11][12][13][14] The COVID-19 pandemic has in uenced the incidence and course of certain diseases. 15,16 The present study explored the demographic and clinical characteristics of patients who developed MEWDS during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…FAF and NIRAF were normal Visual fields 24–2 and 10–2 was within normal limits COVISHIELDTM Vaccination 1 NA NA McMichael et al [ 57 ] Ng et al [ 58 ] Revealed a dome-shaped macula (DSM) with subretinal fluid and interruption of the ellipsoid zone Multiple hyperfluorescent dots in a wreath-like pattern, Late phase indocyanine green angiography revealed hypofluorescent dots in areas corresponding to the autofluorescent fundus lesions. The 30–2 Humphrey visual field test showed enlargement of the blind spot BNT162b2 vaccine 2 NA NA Ng et al [ 58 ] Papasavvas et al [ 75 ] Ellipsoid disruption corresponding to the white lesions with involvement under his fovea, likely causing his reduced vision NA FAF imaging demonstrated typical appearance for MEWDS in the OD with multiple hyperautofluorescent lesions concentrated and coalescing around the disc Pfizer-BioNTech-BioNTech (BNT162b2) COVID-19 vaccine 2 NA NA Papasavvas et al [ 75 ] Papasavvas et al [ 75 ] Focal areas of ellipsoid zone disruption corresponding to the subretinal white lesions on examination, also involving the fovea in her case Demonstrated both early and late hyperfluorescence of the lesions, subtle wreath-like vascular changes around the fovea and late disc leakage FAF imaging demonstrates similar hyperautofluorescent lesions concentrated around the disc Pfizer-BioNTech-BioNTech (BNT162b2) COVID-19 2 NA NA Papasavvas et al [ 75 ] Prieto-Peña et al [ 18 ] The OS revealed multifocal areas of ellipsoid zone (EZ) loss with associated areas of outer retinal hyperreflectivity The OS demonstrated hyperfluorescent staining of the corresponding ar...…”
Section: Resultsmentioning
confidence: 99%
“…The 30–2 Humphrey visual field test showed enlargement of the blind spot BNT162b2 vaccine 2 NA NA Ng et al [ 58 ] Papasavvas et al [ 75 ] Ellipsoid disruption corresponding to the white lesions with involvement under his fovea, likely causing his reduced vision NA FAF imaging demonstrated typical appearance for MEWDS in the OD with multiple hyperautofluorescent lesions concentrated and coalescing around the disc Pfizer-BioNTech-BioNTech (BNT162b2) COVID-19 vaccine 2 NA NA Papasavvas et al [ 75 ] Papasavvas et al [ 75 ] Focal areas of ellipsoid zone disruption corresponding to the subretinal white lesions on examination, also involving the fovea in her case Demonstrated both early and late hyperfluorescence of the lesions, subtle wreath-like vascular changes around the fovea and late disc leakage FAF imaging demonstrates similar hyperautofluorescent lesions concentrated around the disc Pfizer-BioNTech-BioNTech (BNT162b2) COVID-19 2 NA NA Papasavvas et al [ 75 ] Prieto-Peña et al [ 18 ] The OS revealed multifocal areas of ellipsoid zone (EZ) loss with associated areas of outer retinal hyperreflectivity The OS demonstrated hyperfluorescent staining of the corresponding areas FAF of the OS revealed a confluent area of hyperautofluorescence in the posterior pole with scattered hyperautofluorescent dots. Late phase ICG imaging showed diffuse hypocyanescent spots in the posterior pole mRNA-1273 COVID-19 vaccine (Moderna) 2 NA NA Prieto-Peña et al [ 18 ] Roy et al [ 25 ] Revealed thickening of the retina’s outermost layers plus foveal RPE uniformity loss Presented a wreathlike ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation